Job Crafting : A Systematic Review and Meta - Analytical Relationships with Precursors and Work Outcomes (2001 – 2021) - Kumar, Gandhi Vasanth; B., Valarmathi (Prabandhan: Indian Journal of Management, 2022)
Meta-analysis and SEM (structural equation modeling) were used to investigate the relationship between job crafting, job characteristics, work engagement, and job performance. We used random effects of meta-analysis to statistically integrate 199 primary studies and structural equation modeling to examine the assumed moderation through gender and educational levels using Stata: Version 16.0 software. We also ran an exploratory moderator analysis to see any systematic differences in the relationships. The findings revealed that job performance and job characteristics were positively and significantly related at the 1% level, as were job performance, job crafting, and work engagement. All were positively and significantly related at the 1% level. Work engagement and job crafting, too, were positively correlated and statistically significant at the 1% level. Furthermore, p < 0.05 for gender and p < 0.10 for educational level indicated that educational level and gender moderated the relationship between job performance, work engagement, job characteristics, and job crafting significantly. Cronbach’s alpha was used to conduct the reliability test, which indicated a good (0.8 ≤ α < 0.9) and excellent (0.9 ≤ α) internal consistency because Cronbach’s alpha was more significant than the 0.6 thresholds, and the validity indicated that the model was adequate.